Preparation method of double-layer magnetic response hydrogel for 3D printing
Through the preparation method of double-layer magnetic responsive hydrogel, the existing magnetic responsive hydrogel has poor mechanical properties and low 3D printing yields have been solved, and a high toughness and uniform structure of double-layer magnetic responsive hydrogel is achieved, and 4D deformation is achieved under magnetic field conditions.
Patent Information
- Application Number
- CN202411854980.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing magnetic responsive hydrogels have poor mechanical properties, uneven distribution of magnetic particles, and low yield on 3D printing.
The preparation method of a double-layer magnetic responsive hydrogel is adopted, and the unreacted monomer is removed by using a temperature-sensitive deformation gel liquid in a 3D printer and fully swelled in room temperature deionized water after curing under ultraviolet light. Then, the temperature-sensitive hydrogel type is soaked in an aqueous iron salt ion solution to form Fe3O4 magnetic particles, and the magnetic responsive hydrogel type is formed in the NaOH solution, and finally a double-layer structure is formed by bonding.
The mechanical properties and structural uniformity of the 3D-printed double-layer magnetic responsive hydrogel are improved, and the high yield is achieved, and 4D deformation is achieved under the magnetic field conditions generated by the current.
Smart Images

Figure CN119684639A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for 3D printing a magnetically responsive hydrogel, and belongs to the technical field of 3D printing materials. Background Art
[0002] As a special dispersion system, the molecules in gel are connected under certain conditions to form a network structure filled with dispersion medium. Due to its unique properties and internal structure, it has received more and more attention in the fields of drug delivery and biomedicine. Gel materials are combined with other materials with unique properties to give them new functions while retaining the characteristics of gel materials, such as temperature-responsive hydrogels and magnetic hydrogels. Among them, the shape deformation of existing temperature-responsive hydrogels must be triggered in a liquid environment, which greatly limits their application. Magnetic hydrogels generally add Fe3O4 magnetic nanoparticles directly to the hydrogel matrix. The aggregation of magnetic particles in the hydrogel matrix is always a problem. At the same time, the distribution of magnetic particles will significantly affect the mechanical properties of magnetic-responsive hydrogels. The yield rate is low when using 3D printing, which limits their practical application. Summary of the invention
[0003] The present invention aims to solve the technical problems of poor mechanical properties, uneven distribution of magnetic particles and low 3D printing yield of existing magnetic responsive hydrogels, and provide a method for preparing a double-layer magnetic responsive hydrogel for 3D printing. The method for preparing a magnetic responsive hydrogel for 3D printing of the present invention is simple, low in cost and has a high yield of a double-layer hydrogel structure.
[0004] The preparation method of the 3D printed double-layer magnetic responsive hydrogel of the present invention is carried out according to the following steps:
[0005] 1. Weigh 0.1-1 parts of N,N'-methylenebisacrylamide, 0.1-1 parts of photoinitiator, 10-30 parts of water, 5-10 parts of sodium magnesium lithium silicate, 5-10 parts of recrystallized N-isopropylacrylamide and 1-5 parts of dimethylaminopropylmethylacrylamide according to the weight ratio;
[0006] 2. Add N,N'-methylenebisacrylamide and photoinitiator to water in sequence, stir for 5 to 15 minutes, then add sodium magnesium lithium silicate to the aqueous solution in batches under stirring, add the addition within 10 to 30 seconds, and continue stirring until the mixed solution presents a gel state; after the mixed solution presents a gel state, add recrystallized N-isopropylacrylamide and dimethylaminopropylmethylpropionamide to the mixed solution under nitrogen protection, stir for 2 to 3 hours, and then transfer to a centrifuge to remove bubbles in the gel solution to obtain a temperature-sensitive deformation gel solution;
[0007] 3. Add the thermosensitive deformable gel liquid into the 3D printer and perform 3D extrusion printing. After printing and forming, the printing liquid relies on its own self-supporting effect to maintain the printed shape to obtain a gel mold; then transfer the mold to a UV curing lamp for light curing for 2 to 3 minutes to obtain a cured mold; then transfer the cured mold to room temperature deionized water to fully swell and remove unreacted monomers to obtain a thermosensitive hydrogel mold;
[0008] 4. Weigh ferric chloride hexahydrate and ferrous chloride tetrahydrate and add them to deionized water. Stir magnetically to completely dissolve the solid particles to obtain an aqueous solution of iron salt ions. The aqueous solution of iron salt ions contains Fe 2+ with Fe 3+ The molar ratio is 1:1;
[0009] 5. Immerse the thermosensitive hydrogel body after swelling in an aqueous solution of iron salt ions for 36 to 48 hours to allow the thermosensitive hydrogel body to swell fully, thereby obtaining a swollen thermosensitive hydrogel body; the divalent iron ions Fe in the aqueous solution of iron salt ions 2+ With ferric ion Fe 3+ Through the diffusion of water molecules, they enter the gaps in the gel polymer network;
[0010] 6. Transfer the swollen thermosensitive hydrogel body to a NaOH solution and keep it for 20 to 24 hours to obtain a magnetically responsive hydrogel body; in this process, the swollen thermosensitive hydrogel body will quickly turn black after contacting the NaOH solution. This is because the divalent and trivalent iron ions have been transferred to the inside of the gel network before contacting the sodium hydroxide solution. The hydroxide will form Fe3O4 magnetic particles in situ with the iron ions in the gel network during the migration process following the water molecules. After sufficient absorption and reaction, Fe3O4 magnetic particles will be formed in situ inside the gel;
[0011] 7. The thermosensitive hydrogel body obtained in step 3 is bonded to the magnetic responsive hydrogel body obtained in step 6, with the lower layer being the thermosensitive hydrogel and the upper layer being the magnetic responsive hydrogel, to prepare a 3D printed double-layer magnetic responsive hydrogel. The double-layer magnetic responsive hydrogel can undergo a 4D deformation process under the magnetic field conditions generated by the current.
[0012] Furthermore, the photoinitiator in step 1 is (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO);
[0013] Furthermore, in step one, 0.5 to 1 part of N,N'-methylenebisacrylamide, 0.2 to 0.5 part of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 10 to 30 parts of water, 5 to 10 parts of sodium magnesium lithium silicate, 5 to 10 parts of recrystallized N-isopropylacrylamide and 1 to 5 parts of dimethylaminopropylmethylpropionamide are weighed in weight proportion; sodium magnesium lithium silicate is used as a rheology modifier, N,N'-methylenebisacrylamide is used as a chemical cross-linking agent, and N-isopropylacrylamide and dimethylaminopropylmethylpropionamide are used as temperature-sensitive monomers to prepare a temperature-sensitive deformable gel liquid; the temperature-sensitive deformable gel 3D printing liquid synthesized under this condition shows better 3D printing molding stability and yield, and the yield reaches 100%. Different lithium magnesium silicate contents will lead to different fluidity of thermosensitive deformable gel 3D printing liquid. When the weight of lithium magnesium silicate is less than 5 parts, the angle between the liquid surface and the container wall of the printing liquid precursor becomes smaller after being tilted and left to stand for ten minutes. This is because when the lithium magnesium silicate content is low, the printing liquid precursor still has a certain degree of autonomous fluidity, poor shape retention, and cannot be quickly fixed, resulting in the inability to self-support during printing and the inability to achieve accurate 3D printing. When the lithium magnesium silicate content is 5-10 parts, the angle between the liquid surface and the container wall of the printing liquid precursor after tilting and standing, and there is still no obvious change after tilting and standing for ten minutes, indicating that rapid molding and self-support can be achieved when the lithium magnesium silicate content is 5-10 parts. In addition, when the amount of lithium magnesium silicate added is greater than 10 parts, the printing liquid will become more viscous, the fluidity of the printing liquid will deteriorate, and accurate printing and molding cannot be achieved.
[0014] Furthermore, the rotation speed of the centrifuge described in step 2 is 6000 rpm, and the centrifugation time is 5 minutes to obtain the temperature-sensitive deformable gel 3D printing liquid.
[0015] Furthermore, the preparation method of recrystallized N-isopropylacrylamide described in step 2 is as follows: 10 g of NIPAM is weighed and dissolved in toluene, heated to 60° C. in a magnetic stirring water bath at a stirring rate of 400 rpm until completely dissolved, 40 mL of n-hexane is added to the solution, and the solution is kept at 60° C. and stirred for 20 min; toluene and n-hexane are added again, respectively, and the mixture is repeated twice; the mixed solution is filtered to remove the insoluble inhibitor, the filtrate is placed in a -20° C. refrigerator for 12 h, the filtrate is filtered to remove the filtrate, and white flocculent crystals are obtained, and 7 g of NIPAM crystals are obtained by freeze-drying, with a yield of 70%;
[0016] Furthermore, the 3D extrusion printing described in step three has the following specific steps: saving the constructed body model as a file with the suffix -stl format, importing the model into the RepetierHost software to adjust the appropriate printing position and size, slicing the model, and then setting the printer parameters, and then using a dual-head direct writing printer for 3D extrusion printing; the printer parameters are: the extrusion 3D printing equipment used has a printing speed of 10 to 30 mm / s, a Teflon needle with a diameter of 0.4 to 1.2 mm is used as the 3D printing needle, the printing needle height is set between 0.7 and 1.2 mm, and the printing liquid extrusion speed is 10 mm / s.
[0017] Furthermore, the solidified body in step 3 is transferred to deionized water at room temperature to fully swell, which is to immerse the solidified body in deionized water at room temperature for 24 hours to fully swell.
[0018] Furthermore, the wavelength of the ultraviolet curing lamp described in step three is 365nm.
[0019] Furthermore, the magnetic stirring in step 4 is carried out at a stirring rate of 500 to 800 rpm for 20 to 30 min.
[0020] Furthermore, the concentration of ferric chloride hexahydrate in the aqueous solution of iron salt ions in step 4 is 0.05-0.2 mol / L.
[0021] Furthermore, the method for deswelling the thermosensitive hydrogel body in step five is: firstly, the thermosensitive hydrogel body is fully immersed in deionized water at room temperature for 40 to 48 hours to remove unreacted impurities, and then transferred to 80° C. hot water for 1 to 2 hours to shrink and deswell.
[0022] Furthermore, the concentration of the NaOH solution in step five is 1 to 5 mol / L; the mechanical properties of the magnetic hydrogel can be adjusted by changing the concentration of the alkaline solution.
[0023] Furthermore, the bonding method described in step seven is: mixing super glue Loctite 406 and ethyl acetate in a volume ratio of 1:10 to obtain a glue mixture; then bonding the thermosensitive hydrogel body and the magnetic responsive hydrogel body glue mixture to prepare a double-layer magnetic responsive hydrogel.
[0024] The present invention improves the performance of a high-toughness and structurally uniform double-layer magnetically responsive hydrogel that can be used for 3D printing and 4D printing from the following aspects.
[0025] (1) The high-toughness and uniformly structured double-layer magnetically responsive hydrogel for 3D printing of the present invention, wherein the poly(N-isopropylacrylamide) hydrogel matrix is cross-linked by sodium magnesium lithium silicate, and the Fe3O4 magnetic particles are in situ precipitated onto the hydrogel polymer network. The high toughness of the magnetically responsive hydrogel is due to the phase separation of the hydrogel in a high-concentration alkaline solution. The original liquid environment-triggered hydrogel is transformed into a magnetically responsive hydrogel. This shape deformation method using a magnetic field opens up a new method for programming the complex 3D structure of the hydrogel, which can achieve remote control and keep the hydrogel structure away from the liquid environment.
[0026] (2) The present invention adopts extrusion 3D printing to produce thermosensitive hydrogel, and designs a double layer consisting of magnetic responsive hydrogel and thermosensitive hydrogel. The 2D structured double layer can evolve into a 3D shape in an alternating magnetic field (AMF) controlled by the magnetocaloric effect, thus ensuring the perfect realization of 4D printing.
[0027] (3) Prepare DMAPMA composite hydrogel, in which sodium magnesium lithium silicate is uniformly dispersed in the hydrogel matrix. DMAPMA chains are cross-linked with sodium magnesium lithium silicate through non-covalent interactions. Due to hydrogen bonds or ionic or coordination interactions, the magnetic particles are uniformly distributed in the hydrogel, and the fluidity of the thermosensitive deformable gel 3D printing liquid is adjusted by the lithium magnesium silicate content to achieve precise printing and molding.
[0028] The 3D printable, high-toughness, and structurally uniform magnetically responsive hydrogel of the present invention has a residual magnetization intensity of 3.92 to 4.98 emu / g, a Young's modulus of 3.82 to 5.34 kPa, and an elongation at break of 230% to 280%, and can be used in the field of functional hydrogel preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the synthesis process of the thermosensitive magnetic gel in Example 1, (a) thermosensitive gel printing; (b) iron ion solution immersion; (c) magnetic gel synthesis;
[0030] Figure 2 It is a physical sample of the cross-shaped magnetically responsive thermosensitive gel prepared in Example 1;
[0031] Figure 3 This is a diagram of the flower-shaped double-layer magnetic responsive hydrogel prepared in Example 1 undergoing self-folding in an alternating magnetic field;
[0032] Figure 4 This is a magnetic demonstration diagram of the double-layer magnetic responsive hydrogel prepared in Example 1;
[0033] Figure 5 is the XRD spectrum of the double-layer magnetic responsive hydrogel prepared in Examples 1 to 3;
[0034] Figure 6 is a thermogravimetric analysis curve of the double-layer magnetic responsive hydrogel prepared in Examples 1 to 3;
[0035] Figure 7 3 is the hysteresis loop diagram of the double-layer magnetic responsive hydrogel prepared in Examples 1 to 3. DETAILED DESCRIPTION
[0036] The present invention is described in detail below by way of examples. Unless otherwise specified, all raw materials used are commercially available.
[0037] Example 1: The preparation method of the double-layer magnetic responsive hydrogel of this example is carried out according to the following steps:
[0038] 1. Weigh 0.015 g of N,N'-methylenebisacrylamide, 0.015 g of photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 10 mL of deionized water, 0.5 g of sodium magnesium lithium silicate, 0.8 g of recrystallized N-isopropylacrylamide, and 0.2 g of dimethylaminopropylmethylacrylamide; the preparation method of recrystallized N-isopropylacrylamide is as follows: weigh 10 g of N-isopropylacrylamide (NIPAM) and dissolve it in toluene. The mixture was heated to 60°C in a magnetic stirring water bath at a rate of 400 rpm until completely dissolved, 40 mL of n-hexane was added to the solution, and the mixture was kept at 60°C for 20 min. Toluene and n-hexane were added again, and the mixture was repeated twice. The mixed solution was filtered to remove the insoluble inhibitor, and the filtrate was placed in a -20°C refrigerator for 12 h. The filtrate was filtered to remove the filtrate to obtain white flocculent crystals, which were freeze-dried to obtain 7 g of NIPAM crystals with a yield of 70%.
[0039] 2. Add N,N'-methylenebisacrylamide and photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide to deionized water in turn, stir for 10 minutes, then add sodium magnesium lithium silicate to the aqueous solution in batches under stirring, add within 30 seconds, continue stirring for 60 minutes, and the solution presents a gel state; after the solution presents a gel state, add recrystallized N-isopropylacrylamide and dimethylaminopropylmethylpropionamide to the mixed solution under nitrogen protection, stir for 2 hours, then transfer to a centrifuge, centrifuge at a speed of 6000 rpm for 5 minutes to remove bubbles in the gel solution, and obtain a thermosensitive deformation gel solution;
[0040] 3. Save the built body model as a file with the suffix -stl format, import the model into the RepetierHost software to adjust the appropriate printing position and size, slice the model, and then set the printer parameters; the printer parameters are: use a Teflon needle with a diameter of 0.8mm as the 3D printing needle, set the printing needle height at 0.9mm, and the printing liquid extrusion speed at 10mm / s; add the thermosensitive deformable gel liquid to the 3D printer, and then use a double-head direct writing printer for 3D extrusion printing to obtain a gel body; the gel body relies on its own self-supporting effect to maintain the printed shape; then transfer the gel body to a UV curing lamp for light curing for 2 minutes to obtain a cured body; then transfer the cured body to room temperature deionized water and soak it for 48 hours to allow the gel to fully swell and remove unreacted monomers to obtain a thermosensitive hydrogel body;
[0041] 4. Weigh 4 g of ferric chloride hexahydrate and 1.5 g of ferrous chloride tetrahydrate and add them to 100 mL of deionized water. Stir with a magnetic stirrer at a stirring rate of 500 rpm for 20 min to completely dissolve the solid particles to obtain an iron salt ion aqueous solution; wherein the iron salt ion aqueous solution has a concentration of Fe 2+ with Fe 3+ The molar ratio is 1:1;
[0042] 5. First, fully immerse the thermosensitive hydrogel body in deionized water at room temperature for 48 hours to remove unreacted impurities, and then transfer it to 80°C hot water for 2 hours to shrink and reduce swelling; immerse the thermosensitive hydrogel body after swelling in an aqueous solution of iron salt ions for 36 hours to fully swell the thermosensitive hydrogel body to obtain a swollen thermosensitive hydrogel body; the divalent iron ions Fe in the aqueous solution of iron salt ions 2+ With ferric ion Fe 3+ Through the diffusion of water molecules, they enter the gaps in the gel polymer network;
[0043] 6. The swollen thermosensitive hydrogel was transferred to a 3 mol / L NaOH solution and kept for 24 hours to obtain a magnetically responsive hydrogel. In this process, the swollen thermosensitive hydrogel quickly turned black after contacting the NaOH solution. This is because the divalent and trivalent iron ions had been transferred to the inside of the gel network before contacting the sodium hydroxide solution. The hydroxide ions would form Fe3O4 magnetic particles in situ with the iron ions in the gel network during the migration process following the water molecules. After sufficient absorption and reaction, Fe3O4 magnetic particles would be formed in situ in the gel.
[0044] 7. Mix Loctite 406 and ethyl acetate in a volume ratio of 1:10 to obtain a glue mixture; use the thermosensitive hydrogel body obtained in step 3 as the lower layer and the magnetic responsive hydrogel body obtained in step 6 as the upper layer, apply the glue mixture between the upper and lower layers for bonding, and prepare a 3D printed double-layer magnetic responsive hydrogel. The double-layer magnetic responsive hydrogel can undergo a 4D deformation process under the magnetic field generated by the current.
[0045] Figure 1 This is a schematic diagram of the process of obtaining the magnetically responsive hydrogel body in step 6 from the thermosensitive hydrogel body in step 3 and the swollen thermosensitive hydrogel body in step 5 in Example 1; wherein a is the thermosensitive hydrogel body in step 3, b is the swollen thermosensitive hydrogel body in step 5, and c is the magnetically responsive hydrogel body in step 6.
[0046] Figure 2 These are photos of the actual sample of the cross-shaped double-layer magnetically responsive hydrogel prepared in step six of Example 1. a is the temperature-sensitive hydrogel printed by 3D printing, b is the magnetically responsive hydrogel generated by the in-situ precipitation method, and c is the magnetic force test diagram of the magnetically responsive hydrogel. It can be seen from c that the magnetically responsive hydrogel can be sucked up by a magnet.
[0047] Figure 3 The petal-shaped double-layer magnetic responsive hydrogel sample of Example 1 is placed in a coil. The coil is energized to form a magnetic field. The petal-shaped double-layer magnetic responsive hydrogel sample deforms under the magnetic field condition as shown in FIG. Figure 3 As shown, the entire deformation process takes 4.5 minutes, and the thermosensitive hydrogel body in the lower layer can maintain a stable gel state without fluidity under this condition.
[0048] Figure 4 This is a magnetic demonstration diagram of the double-layer magnetic responsive hydrogel prepared in Example 1. Figure 4 As can be seen in the figure, the double-layer magnetically responsive hydrogel can be moved by the external magnetic field.
[0049] Example 2: The preparation method of the double-layer magnetic responsive hydrogel of this example is carried out according to the following steps:
[0050] 1. Weigh 0.03 g of N,N'-methylenebisacrylamide, 0.03 g of photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 10 mL of deionized water, 1 g of sodium magnesium lithium silicate, 0.7 g of recrystallized N-isopropylacrylamide and 0.3 g of dimethylaminopropylmethylacrylamide; wherein the preparation method of recrystallized N-isopropylacrylamide is the same as that of Example 1;
[0051] 2. Add N,N'-methylenebisacrylamide and photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide to deionized water in turn, stir for 10 minutes, then add sodium magnesium lithium silicate to the aqueous solution in batches under stirring, add within 30 seconds, continue stirring for 60 minutes, and the solution presents a gel state; after the solution presents a gel state, add recrystallized N-isopropylacrylamide and dimethylaminopropylmethylpropionamide to the mixed solution under nitrogen protection, stir for 2 hours, then transfer to a centrifuge, centrifuge at a speed of 6000 rpm for 5 minutes to remove bubbles in the gel solution, and obtain a thermosensitive deformation gel solution;
[0052] 3. Save the built body model as a file with the suffix -stl format, import the model into the RepetierHost software to adjust the appropriate printing position and size, slice the model, and then set the printer parameters; the printer parameters are: use a Teflon needle with a diameter of 0.8mm as the 3D printing needle, set the printing needle height at 1.1mm, and the printing liquid extrusion speed at 20mm / s; add the thermosensitive deformable gel liquid to the 3D printer, and then use a double-head direct writing printer for 3D extrusion printing to obtain a gel body; the gel body relies on its own self-supporting effect to maintain the printed shape; then transfer the gel body to a UV curing lamp for light curing for 2 minutes to obtain a cured body; then transfer the cured body to room temperature deionized water and soak it for 48 hours to allow the gel to fully swell and remove unreacted monomers to obtain a thermosensitive hydrogel body;
[0053] 4. Weigh 4 g of ferric chloride hexahydrate and 1.5 g of ferrous chloride tetrahydrate and add them to 100 mL of deionized water. Stir with a magnetic stirrer at a stirring rate of 500 rpm for 20 min to completely dissolve the solid particles to obtain an iron salt ion aqueous solution; wherein the iron salt ion aqueous solution has a concentration of Fe 2+ with Fe 3+ The molar ratio is 1:1;
[0054] 5. First, fully immerse the thermosensitive hydrogel body in deionized water at room temperature for 48 hours to remove unreacted impurities, and then transfer it to 80°C hot water for 2 hours to shrink and reduce swelling; immerse the thermosensitive hydrogel body after swelling in an aqueous solution of iron salt ions for 36 hours to fully swell the thermosensitive hydrogel body to obtain a swollen thermosensitive hydrogel body; the divalent iron ions Fe in the aqueous solution of iron salt ions 2+ With ferric ion Fe 3+ Through the diffusion of water molecules, they enter the gaps in the gel polymer network;
[0055] 6. The swollen thermosensitive hydrogel was transferred to a NaOH solution with a concentration of 4 mol / L and kept for 24 hours to obtain a magnetically responsive hydrogel. In this process, the swollen thermosensitive hydrogel quickly turned black after contacting the NaOH solution. This is because the divalent and trivalent iron ions had been transferred to the inside of the gel network before contacting the sodium hydroxide solution. The hydroxide ions would form Fe3O4 magnetic particles in situ with the iron ions in the gel network during the migration process following the water molecules. After sufficient absorption and reaction, Fe3O4 magnetic particles would be formed in situ in the gel.
[0056] 7. Mix Loctite 406 and ethyl acetate in a volume ratio of 1:10 to obtain a glue mixture; use the thermosensitive hydrogel body obtained in step 3 as the lower layer and the magnetic responsive hydrogel body obtained in step 6 as the upper layer, apply the glue mixture between the upper and lower layers for bonding, and prepare a 3D printed double-layer magnetic responsive hydrogel. The double-layer magnetic responsive hydrogel can undergo a 4D deformation process under the magnetic field generated by the current.
[0057] The double-layer magnetic responsive hydrogel prepared in Example 2 can be deformed under magnetic field conditions, and the entire deformation process takes 5 minutes. The lower layer of thermosensitive hydrogel can maintain a stable gel state under these conditions without fluidity.
[0058] Example 3: The preparation method of the double-layer magnetic responsive hydrogel of this example is carried out according to the following steps:
[0059] 1. Weigh 0.015 g of N,N'-methylenebisacrylamide, 0.015 g of photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 10 mL of deionized water, 1 g of sodium magnesium lithium silicate, 0.7 g of recrystallized N-isopropylacrylamide and 0.3 g of dimethylaminopropylmethylacrylamide; wherein the preparation method of recrystallized N-isopropylacrylamide is the same as that of Example 1;
[0060] 2. Add N,N'-methylenebisacrylamide and photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide to deionized water in turn, stir for 10 minutes, then add sodium magnesium lithium silicate to the aqueous solution in batches under stirring, add within 30 seconds, continue stirring for 60 minutes, and the solution presents a gel state; after the solution presents a gel state, add recrystallized N-isopropylacrylamide and dimethylaminopropylmethylpropionamide to the mixed solution under nitrogen protection, stir for 2 hours, then transfer to a centrifuge, centrifuge at a speed of 6000 rpm for 5 minutes to remove bubbles in the gel solution, and obtain a thermosensitive deformation gel solution;
[0061] 3. Save the built body model as a file with the suffix -stl format, import the model into the RepetierHost software to adjust the appropriate printing position and size, slice the model, and then set the printer parameters; the printer parameters are: printing speed is 20mm / s, a Teflon needle with a diameter of 1.2mm is used as the 3D printing needle, the printing needle height is set at 0.9mm, and the printing liquid extrusion speed is 20mm / s; add the thermosensitive deformable gel liquid to the 3D printer, and then use a double-head direct writing printer for 3D extrusion printing to obtain a gel body; the gel body relies on its own self-supporting effect to maintain the printed shape; then transfer the gel body to a UV curing lamp for light curing for 2 minutes to obtain a cured body; then transfer the cured body to room temperature deionized water and soak for 48 hours to allow the gel to fully swell and remove unreacted monomers to obtain a thermosensitive hydrogel body;
[0062] 4. Weigh 3.5 g of ferric chloride hexahydrate and 2 g of ferrous chloride tetrahydrate and add them to 100 mL of deionized water. Stir with a magnetic stirrer at a stirring rate of 500 rpm for 20 min to completely dissolve the solid particles to obtain an iron salt ion aqueous solution; wherein the iron salt ion aqueous solution has a concentration of Fe 2+ with Fe 3+ The molar ratio is 1:1;
[0063] 5. First, fully immerse the thermosensitive hydrogel body in deionized water at room temperature for 48 hours to remove unreacted impurities, and then transfer it to 80°C hot water for 2 hours to shrink and reduce swelling; immerse the thermosensitive hydrogel body after swelling in an aqueous solution of iron salt ions for 36 hours to fully swell the thermosensitive hydrogel body to obtain a swollen thermosensitive hydrogel body; the divalent iron ions Fe in the aqueous solution of iron salt ions 2+ With ferric ion Fe 3+ Through the diffusion of water molecules, they enter the gaps in the gel polymer network;
[0064] 6. The swollen thermosensitive hydrogel was transferred to a NaOH solution with a concentration of 5 mol / L and kept for 24 hours to obtain a magnetically responsive hydrogel. In this process, the swollen thermosensitive hydrogel quickly turned black after contacting the NaOH solution. This is because the divalent and trivalent iron ions had been transferred to the inside of the gel network before contacting the sodium hydroxide solution. The hydroxide ions would form Fe3O4 magnetic particles in situ with the iron ions in the gel network during the migration process following the water molecules. After sufficient absorption and reaction, Fe3O4 magnetic particles would be formed in situ in the gel.
[0065] 7. Mix Loctite 406 and ethyl acetate in a volume ratio of 1:10 to obtain a glue mixture; use the thermosensitive hydrogel body obtained in step 3 as the lower layer and the magnetic responsive hydrogel body obtained in step 6 as the upper layer, apply the glue mixture between the upper and lower layers for bonding, and prepare a 3D printed double-layer magnetic responsive hydrogel. The double-layer magnetic responsive hydrogel can undergo a 4D deformation process under the magnetic field generated by the current.
[0066] The double-layer magnetic responsive hydrogel sample of this embodiment can be deformed under magnetic field conditions, and the entire deformation process takes 5.2 minutes. The lower layer of thermosensitive hydrogel can maintain a stable gel state without fluidity under this condition.
[0067] The double-layer magnetic responsive hydrogels prepared in Examples 1 to 3 were subjected to XRD testing, and the obtained XRD spectra were as follows: Figure 5 As shown, from Figure 5 It can be seen that the characteristic peak in the spectrum matches the peak of Fe3O4, indicating that the double-layer magnetic responsive hydrogel contains Fe3O4 particles. At the same time, the sizes of Fe3O4 particles in the double-layer magnetic responsive hydrogels prepared in Examples 1 to 3 are not much different.
[0068] The double-layer magnetic responsive hydrogel prepared in Examples 1 to 3 was subjected to thermogravimetric analysis, and the obtained thermogravimetric curves are as follows: Figure 6 As shown, from Figure 6 It can be seen that during the heat treatment of the double-layer magnetic responsive hydrogel, as the temperature rises, water will vaporize, and most of the polymer materials will be ablated, and the remaining is mainly inorganic matter, such as iron oxide. Compared with the double-layer magnetic responsive hydrogels prepared in Examples 1 to 3, the double-layer magnetic responsive hydrogel in Example 1 has the highest residual weight, indicating that its iron oxide content is the highest. The basis of the magnetic responsive hydrogel is to contain magnetic Fe3O4, so the iron content is the highest and should have the best magnetic response.
[0069] The double-layer magnetic responsive hydrogel prepared in Examples 1 to 3 was subjected to a hysteresis loop test, and the obtained hysteresis loop diagram is as follows: Figure 7 As shown, from Figure 7 It can be seen that the double-layer magnetic responsive hydrogels prepared in Examples 1 to 3 all exhibit obvious superparamagnetic behavior, among which the double-layer magnetic responsive hydrogel prepared in Example 1 has the largest residual magnetization intensity of 4.98emu / g. The residual magnetization intensity of the double-layer magnetic responsive hydrogel prepared in Example 2 is 4.14emu / g, and the residual magnetization intensity of the double-layer magnetic responsive hydrogel prepared in Example 3 is 3.92emu / g.
[0070] The mechanical properties of the double-layer magnetic responsive hydrogels prepared in Examples 1 to 3 were tested, and the obtained mechanical properties are shown in Table 1.
[0071] Table 1 Mechanical properties of double-layer magnetic responsive hydrogels prepared in Examples 1 to 3
[0072] sample Young's modulus(kPa) Elongation at break (%) Example 1 4.54 280 Example 2 5.34 260 Example 3 3.82 230
[0073] Example 4: The preparation method of the double-layer magnetic responsive hydrogel of this example is carried out according to the following steps:
[0074] 1. Weigh 0.015 g of N,N'-methylenebisacrylamide, 0.015 g of photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 10 mL of deionized water, 1.5 g of sodium magnesium lithium silicate, 0.8 g of recrystallized N-isopropylacrylamide and 0.2 g of dimethylaminopropylmethylacrylamide; wherein the preparation method of recrystallized N-isopropylacrylamide is the same as that of Example 1;
[0075] 2. Add N,N'-methylenebisacrylamide and photoinitiator (2,4,6-trimethylbenzoyl) diphenylphosphine oxide to deionized water in turn, stir for 10 minutes, then add sodium magnesium lithium silicate to the aqueous solution in batches under stirring, add within 30 seconds, continue stirring for 60 minutes, and the solution presents a gel state; after the solution presents a gel state, add recrystallized N-isopropylacrylamide and dimethylaminopropylmethylpropionamide to the mixed solution under nitrogen protection, stir for 2 hours, then transfer to a centrifuge, centrifuge at a speed of 6000 rpm for 5 minutes to remove bubbles in the gel solution, and obtain a thermosensitive deformation gel solution;
[0076] 3. Save the built body model as a file with the suffix -stl format, import the model into the RepetierHost software to adjust the appropriate printing position and size, slice the model, and then set the printer parameters; the printer parameters are: use a Teflon needle with a diameter of 0.8mm as the 3D printing needle, set the printing needle height at 0.9mm, and the printing liquid extrusion speed at 10mm / s; add the thermosensitive deformable gel liquid to the 3D printer, and then use a double-head direct writing printer for 3D extrusion printing to obtain a gel body; the gel body relies on its own self-supporting effect to maintain the printed shape; then transfer the gel body to a UV curing lamp for light curing for 2 minutes to obtain a cured body; then transfer the cured body to room temperature deionized water and soak it for 48 hours to allow the gel to fully swell and remove unreacted monomers to obtain a thermosensitive hydrogel body;
[0077] 4. Add 4.0 g of ferric chloride hexahydrate and 1.5 g of ferrous chloride tetrahydrate into 100 mL of deionized water, and stir with a magnetic stirrer at a stirring rate of 500 rpm for 20 min to completely dissolve the solid particles to obtain an aqueous solution of iron salt ions; wherein the aqueous solution of iron salt ions contains Fe 2+ with Fe 3+The molar ratio is 1:1;
[0078] 5. First, fully immerse the thermosensitive hydrogel body in deionized water at room temperature for 48 hours to remove unreacted impurities, and then transfer it to 80°C hot water for 2 hours to shrink and reduce swelling; immerse the thermosensitive hydrogel body after swelling in an aqueous solution of iron salt ions for 36 hours to fully swell the thermosensitive hydrogel body to obtain a swollen thermosensitive hydrogel body; the divalent iron ions Fe in the aqueous solution of iron salt ions 2+ With ferric ion Fe 3+ Through the diffusion of water molecules, they enter the gaps in the gel polymer network;
[0079] 6. The swollen thermosensitive hydrogel was transferred to a 3 mol / L NaOH solution and kept for 24 hours to obtain a magnetically responsive hydrogel. In this process, the swollen thermosensitive hydrogel quickly turned black after contacting the NaOH solution. This is because the divalent and trivalent iron ions had been transferred to the inside of the gel network before contacting the sodium hydroxide solution. The hydroxide ions would form Fe3O4 magnetic particles in situ with the iron ions in the gel network during the migration process following the water molecules. After sufficient absorption and reaction, Fe3O4 magnetic particles would be formed in situ in the gel.
[0080] 7. Mix Loctite 406 and ethyl acetate in a volume ratio of 1:10 to obtain a glue mixture; use the thermosensitive hydrogel body obtained in step 3 as the lower layer and the magnetic responsive hydrogel body obtained in step 6 as the upper layer, apply the glue mixture between the upper and lower layers for bonding, and prepare a 3D printed double-layer magnetic responsive hydrogel. The double-layer magnetic responsive hydrogel can undergo a 4D deformation process under the magnetic field generated by the current.
[0081] The double-layer magnetic responsive hydrogel sample prepared in this embodiment can be deformed under magnetic field conditions. The entire deformation process takes 4.9 minutes. Under this condition, the thermosensitive gel in the lower layer maintains a stable gel state without fluidity.
[0082] The double-layer magnetic responsive hydrogel prepared in this embodiment has a residual magnetization intensity of 4.53emu / g, a Young's modulus of 5.13kPa, and an elongation at break of 270%.
Claims
1. A method for preparing a 3D printed double-layer magnetically responsive hydrogel, characterized in that: The method proceeds as follows:
1. Weigh 0.1-1 parts of N,N'-methylenebisacrylamide, 0.1-1 parts of photoinitiator, 10-30 parts of water, 5-10 parts of sodium magnesium lithium silicate, 5-10 parts of recrystallized N-isopropylacrylamide and 1-5 parts of dimethylaminopropylmethylacrylamide according to the weight ratio; 2. Add N,N'-methylenebisacrylamide and photoinitiator to water in sequence, stir for 5 to 15 minutes, then add sodium magnesium lithium silicate to the aqueous solution in batches under stirring, add the addition within 10 to 30 seconds, and continue stirring until the mixed solution presents a gel state; after the mixed solution presents a gel state, add recrystallized N-isopropylacrylamide and dimethylaminopropylmethylpropionamide to the mixed solution under nitrogen protection, stir for 2 to 3 hours, and then transfer to a centrifuge to remove bubbles in the gel solution to obtain a temperature-sensitive deformation gel solution; 3. Add the thermosensitive deformable gel liquid into the 3D printer and perform 3D extrusion printing. After printing and forming, the printing liquid relies on its own self-supporting effect to maintain the printed shape to obtain a gel mold; then transfer the mold to a UV curing lamp for light curing for 2 to 3 minutes to obtain a cured mold; then transfer the cured mold to room temperature deionized water to fully swell and remove unreacted monomers to obtain a thermosensitive hydrogel mold; 4. Weigh ferric chloride hexahydrate and ferrous chloride tetrahydrate and add them to deionized water. Stir magnetically to completely dissolve the solid particles to obtain an aqueous solution of iron salt ions. The aqueous solution of iron salt ions contains Fe 2+ with Fe 3+ The molar ratio is 1:1; 5. immersing the deswelled thermosensitive hydrogel body in an aqueous solution of iron salt ions for 36 to 48 hours to allow the thermosensitive hydrogel body to swell fully, thereby obtaining a swollen thermosensitive hydrogel body; 6. Transfer the swollen thermosensitive hydrogel body to a NaOH solution and keep it for 20 to 24 hours to obtain a magnetically responsive hydrogel body; 7. The thermosensitive hydrogel body obtained in step 3 is bonded to the magnetically responsive hydrogel body obtained in step 6, with the lower layer being the thermosensitive hydrogel and the upper layer being the magnetically responsive hydrogel, to prepare a 3D printed double-layer magnetically responsive hydrogel.
2. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1, characterized in that: The photoinitiator described in step 1 is (2,4,6-trimethylbenzoyl) diphenylphosphine oxide.
3. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: In step 1, 0.5 to 1 part of N,N'-methylenebisacrylamide, 0.2 to 0.5 part of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 10 to 30 parts of water, 5 to 10 parts of sodium magnesium lithium silicate, 5 to 10 parts of recrystallized N-isopropylacrylamide and 1 to 5 parts of dimethylaminopropylmethylacrylamide are weighed in proportion by weight.
4. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The preparation method of recrystallized N-isopropylacrylamide described in step 1 is as follows: weigh 10g NIPAM and dissolve it in toluene, heat it to 60°C in a magnetic stirring water bath at a stirring rate of 400rpm until it is completely dissolved, add 40mL of n-hexane to the solution, keep it at a constant temperature of 60°C and stir for 20min; add toluene and n-hexane again, respectively, and repeat twice; filter the mixed solution to remove the insoluble inhibitor, let the filtrate stand in a -20°C refrigerator for 12h, filter the filtrate to obtain white flocculent crystals, and obtain NIPAM crystals by freeze-drying.
5. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The specific steps of 3D extrusion printing described in step three are: save the built body model as a file with the suffix -stl format, import the model into the RepetierHost software to adjust the printing position and size, slice the model, and then set the printer parameters, and then use a double-head direct writing printer for 3D extrusion printing; the printer parameters are: the extrusion 3D printing equipment used has a printing speed of 10 to 30 mm / s, a Teflon needle with a diameter of 0.4 to 1.2 mm is used as the 3D printing needle, the printing needle height is set between 0.7 and 1.2 mm, and the printing liquid extrusion speed is 10 mm / s.
6. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The solidified body described in step 3 is transferred to deionized water at room temperature to fully swell, which is to immerse the solidified body in deionized water at room temperature for 24 hours to fully swell.
7. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The wavelength of the ultraviolet curing lamp described in step 3 is 365nm.
8. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The method for deswelling the thermosensitive hydrogel body described in step 5 is: first, fully immerse the thermosensitive hydrogel body in deionized water at room temperature for 40 to 48 hours to remove unreacted impurities, and then transfer it to 80° C. hot water and keep it for 1 to 2 hours to shrink and deswell.
9. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The concentration of the NaOH solution described in step 5 is 1-5 mol / L.
10. The method for preparing a 3D printed double-layer magnetic responsive hydrogel according to claim 1 or 2, characterized in that: The bonding method described in step seven is: mixing super glue Loctite 406 and ethyl acetate in a volume ratio of 1:10 to obtain a glue mixture; then bonding the thermosensitive hydrogel body and the magnetic responsive hydrogel body with the glue mixture to prepare a double-layer magnetic responsive hydrogel.
Citation Information
Patent Citations
Preparation method of 3D printed hydrogel and application of prepared hydrogel
CN111434698A
Temperature-sensitive hydrogel elastomer hydrophilic and hydrophobic material capable of being subjected to 4D printing as well as preparation method and application of temperature-sensitive hydrogel elastomer hydrophilic and hydrophobic material
CN115141320A
Magnetic temperature-sensitive double-layer hydrogel as well as preparation method and application thereof
CN118667061A
Method of 4d printing a hydrogel composite structure
US20170151733A1